The Relation of Company Risk, Liquidity, Leverage, Capital Adequacy and Earning Management: Evidence from Indonesia Banking Companies - Religiosa, Maria Wrightia; Surjandari, Dwi Asih (Mediterranean Journal of Social Sciences, 2021)
The aim of this study is to analyze the effect of Company Risk, Liquidity, Leverage and Capital Adequacy Ratio on Earning Management and whether Capital Adequacy Ratio moderates the relation between Company Risk, Liquidity and Leverage and Earning Management of Banking Companies listed in Indonesia Stock Exchange during 2014-2018. Sampling techniques uses purposive sampling based on determined criteria and data analysis is performed by multiple regression analysis using E-Views 11.0 version. The result shows that in partial, Company Risk positively, Liquidity and Capital Adequacy negatively affects significantly on Earning Management, while Leverage does not and in the other side Capital Adequacy Ratio only moderates the relation between Liquidity and Earning Management. All variables simultaneously affect weakly on Earning Management. This research implies that due to weakly impact result, banking management must reobserve the role of Company Risk, Liquidity, Leverage and Capital Adequacy Ratio in executing Earning Management. Received: 7 October 2020 / Accepted: 10 November 2020/ Published: 17 January 2021